Open your eyes - Gavin Sinclair (Scottish Journal of Residential Child Care)
In May this year I wrote an article about a theatre play called 'Please Listen' and its successes. Today I'd like to tell you about the development of this work, about stability, opportunity, belief, support, communication, continuity, prospects and a young man's determination to succeed in life. Lots of buzz words used in that sentence, but none without justification. Let me explain.